1982
DOI: 10.1159/000176582
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intestinal Function in Response to Thyroxine and Cortisone Administration in Undernourished Rats

Abstract: Imposition of undernutrition during the suckling period considerably enhanced the intestinal uptake of D-glucose and glycine compared to a control group. Brush border sucrase, and alkaline phosphatase activities were drastically reduced while lactase and leucine amino peptidase levels were significantly elevated at weaning in nutritionally deprived pups as compared to control animals. Cortisone administration to undernourished rats depressed the uptake of D-glucose but stimulated that of glycine. Thyroxine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In conclusion, the present findings sup port the contention [5,6] that UN imposed during the suckling period delays the maturational development of intestine, as evi denced by increased sialylation and de creased fucosylation processes, characteris tics of the immature tissue [2], Administra tion of cortisone and insulin induced adulttype changes in glycosylation of MVM in nutritionally deprived pups. This further corroborates the contention that the sialyla tion and fucosylation of MVM are in fluenced by hormone treatments in suckling pups [4.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In conclusion, the present findings sup port the contention [5,6] that UN imposed during the suckling period delays the maturational development of intestine, as evi denced by increased sialylation and de creased fucosylation processes, characteris tics of the immature tissue [2], Administra tion of cortisone and insulin induced adulttype changes in glycosylation of MVM in nutritionally deprived pups. This further corroborates the contention that the sialyla tion and fucosylation of MVM are in fluenced by hormone treatments in suckling pups [4.…”
Section: Discussionsupporting
confidence: 73%
“…Thus the observed decrease in sucrase to gether with an enhanced lactase level in UN intestine suggests delayed maturation of in testinal tissue in nutritionally deprived ani mals [5,6]. The chemical analysis as well as the lectin binding data indicated that impo sition of UN during suckling period stimu lates sialylation and reduces fucosylation of microvillus surface in intestine.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…yGT, in addition to its hydrolytic function, is involved in peptide transport (Tate and Meister 1974;Griffith and Meister 1980). AP activity is induced by all the phosphorylated substrates, phospholipids and phosphoproteins (Shirazi et al 1978;McCarthy et al 1980) and is a sensitive indicator of malnutrition status (Kumar and Chase 1971;Pathak et al 1982). Poorest growth was observed in the MP group and, yet, this group had higher specific activity for the three intestinal enzymes assayed in whole body homogenates.…”
Section: Enzyme Adaptation To Dietmentioning
confidence: 99%